Kinetics of Cd, Co and Ni Adsorption from Wastewater using Red and Black Tea Leaf Blend as a Bio-adsorbent - Ziarati, Parisa; Kozub, Pavlo; Vambol, Sergij; Vambol, Viola; Khan, Nadeem A.; Kozub, Svetlana; Tajik, Sepideh (Ecological Questions, 2020)
Every year there is deterioration in water quality. This is due to human activity. The current environmental strategies of many countries motivate the scientific community to develop reliable, economically viable and environmentally friendly technologies that are able to remove pollutants from the environment, including water. The study purpose is to determine of influence regularity of the bio-adsorbent composition and amount, which consists of red and black tea leaves mixture, on the Cd, Co and Ni adsorption process based on experimental data. As well as determine the most rational bio-adsorbent dose and the necessary red and black tea dose in bio-adsorbent to achieve MPC of heavy metals, with which process duration will be minimal. Initially, to study the adsorption process kinetics, the nature of the curve that describes the obtained experimental values was visually analyzed. To determine the adsorption process kinetic regularity, which most adequately and reliably describes the experimental data and to determine the values of the coefficients in the exponential regularity, the least squares method was used. It was observed that for Cd and Co, an increase in the black and red tea amount leads to a drastic reduction of the adsorption process time (up to 10 times); while for Ni the black tea addition slows down the adsorption process. Ni adsorption is the most complex and for certain bio-adsorbent composition values, complete Ni removal cannot be achieved in a technologically reasonable adsorption time. The technological process of Cd, Co and Ni adsorption can be expedient, if it is carried out in several stages with optimal red and black tea amounts for each of the metals. Adsorption process kinetic regularity, which was determined, can be used to calculate of adsorption process technological parameters in values wide range.